2018
DOI: 10.1021/acs.macromol.8b01966
|View full text |Cite
|
Sign up to set email alerts
|

Brush-First and ROMP-Out with Functional (Macro)monomers: Method Development, Structural Investigations, and Applications of an Expanded Brush-Arm Star Polymer Platform

Abstract: The efficient synthesis of complex functional polymeric nanomaterials is often challenging. Ru-initiated ring-opening metathesis polymerization (ROMP) of multivalent macromonomers followed by cross-linking to form brush-arm star (BASP) polymers enables access to well-defined nano-structures with diverse functionality. This “brush-first” method leaves active Ru in the BASP microgel core, which could potentially be used in a subsequent “ROMP-out” (RO) step to introduce further modifications to the BASP structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 54 publications
(98 reference statements)
0
23
0
Order By: Relevance
“…Johnson and co-workers have pioneered the use of ROMP to construct “core-cross-linked” molecules termed “mikto-brush-arm star polymers” that bear some similarities to the materials described herein. Their synthetic method also leverages the benefits of ROMP to build arms via macromonomer copolymerization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Johnson and co-workers have pioneered the use of ROMP to construct “core-cross-linked” molecules termed “mikto-brush-arm star polymers” that bear some similarities to the materials described herein. Their synthetic method also leverages the benefits of ROMP to build arms via macromonomer copolymerization.…”
Section: Resultsmentioning
confidence: 99%
“…The key distinction is a final step involving the addition of multifunctional norbornene cross-linker, which forms a compact core that polymerized macromonomers protrude from. Such core-cross-linking has undoubtedly proven useful in a variety of applications, but the molecular connectivity is fundamentally different compared to low- N BB statistical and block bottlebrush polymers. No cross-linking step is involved in our approach and the core of each star polymer is precisely the well-defined poly­(norbornene) backbone that is formed during ROMP in the absence of multifunctional additives.…”
Section: Resultsmentioning
confidence: 99%
“…[237][238][239] Among them, BBPs present distinctive features for efficient nanoscale encapsulation and delivery agents. [17][18][19]240,241 Cylindrical structures of BBPs can increase the retention of drug molecules and cell-or tissue-selective targeting. 17,242 The high functionality of BBPs affords a large loading of drug molecules, as they can be readily attached to the end groups of sidechains 18 or coupled to the backbone.…”
Section: Solution Assembly and Drug Deliverymentioning
confidence: 99%
“…17,242 The high functionality of BBPs affords a large loading of drug molecules, as they can be readily attached to the end groups of sidechains 18 or coupled to the backbone. 240,241 These advantages have led to rigorous research into applying BBPs in the drug delivery field.…”
Section: Solution Assembly and Drug Deliverymentioning
confidence: 99%
“…Garle et al investigated the interactions between vesicle membrane and the bottlebrush polymers, whose side chains consisted of polyethylene glycol (PEG); they found that compared with ungrafted cationic polymers, molecular brushes with PEG as the side chain have significant film penetration ability because the side chains are more likely to be inserted into the phospholipid membranes [22]. Golder et al obtained a similar conclusion that the increased density of PEG side chains helped the nanoparticles enter the cell [23]. Liu et al used the electrostatic interaction between the polyelectrolyte brush and the oppositely charged membrane vesicles to form a flat cell membrane double layer from the vesicles [24].…”
Section: Introductionmentioning
confidence: 99%